Observation in Bulgaria of a Griffon Vulture Gyps fulvus tagged in Spain. Issue 1 (2nd January 2019) - Stoyanov, Georgi; Peshev, Hristo; Kmetova-Biro, Elena; Opramolla, Giancarlo; Casado, Carlos Moreno; Posillico, Mario; Licheva, Vanya; Stoynov, Emilian
ABSTRACT: Griffon Vultures are found throughout the Mediterranean Basin, with the largest population being in Spain. Since 1973, several thousand Griffon Vultures have been ringed in Spain with metal or plastic rings. Here we report the movement of one of these birds discovered 2300 km away from the ringing site, ten years later, with several observations during this period in different places in France, Italy and Bulgaria.